Facade 4.0 – The new digital life-cycle of the building envelope - Arztmann, Daniel; Ramirez, Jhosangela; Mena Lozada , Tomas (Facade Tectonics 2020 World Congress)
Urban noise pollution is a major environmental health problem. International organizations are making efforts to prevent health damage due to high levels of noise in cities, but the design of the built environment typically neglects the acoustic impact of architectural projects. Building facades, covering a substantial part of the vertical surfaces of the urban fabric, have a significant effect on the wellbeing of the population and on the environmental impact of buildings. Facade geometries and materials interact with the diversity of sounds in the city composing soundscapes that influence the health, comfort, and productivity of people inside and outside of buildings. This study gives an overview of the elements involved in the composition of the urban soundscape and revises the potential effects of sound-reflective and sound-absorptive facades. With the purpose of exemplifying the integration of acoustic data into facade design processes, a parametric design workflow is developed to experiment with acoustic simulations of a street environment, alternating between sound-reflective and sound-absorptive facades.
Keywords: acoustics; sustainability; computational design; parametric workflows